Making Sense of the Obesity Paradox - Hoyle, Brian (MD Conference Express, 2014)
The obesity paradox can be described as the tendency for obese individuals, including those with chronic diseases, to survive longer than adults of normal weight as determined by body mass index. This article discusses data, as well as possible explanations.